(untitled) (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
This article is the result of the study on the description of the development of hadith studies in Aceh after the determination of Islamic law. The assertion of Aceh as the Sharia region indicates that referring to the source of sharia is the Koran and hadith. The reality in the field at a glance shows that the study of the hadith in the sharia has not gone through the progress of the implementation of the sharia itself. The criticism of the hadith is still a taboo, but the hadith of the hadith has not referred to its source (Maṣādir al-Aṣliyah). The research was conducted by interviewing research subjects as many as 10 (ten) people from the academic community, and from among the Dayah in Banda Aceh and Aceh Besar. The results showed that academics were important with the study of hadith despite being admitted that the development of the Hadith studies has not shown its title. Three factors affect the ungrowing study of hadith. Firstly, there are no teachers in the hadith. Secondly, the strong attachment to the sect is one of the constraints of the study of Hadith. Thirdly, there has been no concern and seriousness towards the study of hadith by academics Abstrak: Artikel ini merupakan hasil penelitian tentang deskripsi perkembangan studi hadist di Aceh setelah penetapan syariat Islam. Penegasan Aceh sebagai wilayah syariat mengindikasikan bahwa merujuk kepada sumber syariat yaitu Alquran dan hadist. Realitas di lapangan yang dicermati secara sekilas menunjukkan bahwa studi hadist di wilayah syariat belum berjalan beriring dengan kemajuan pelaksanaan syariat itu sendiri. Wacana kritik hadist masih menjadi tabu, pengutipan hadist belum merujuk pada sumber aslinya (maṣādir al-aṣliyah). Penelitian ini dilakukan dengan mewawancarai subjek penelitian sebanyak 10 (sepuluh) orang dari kalangan akademik, dan dari kalangan dayah di Kota Banda Aceh dan Kabupaten Aceh Besar. Hasil penelitian menunjukkan bahwa para akademisi merasa penting dengan studi hadist meskipun diakui bahwa perkembangan studi hadist belum menunjukkan geliatnya. Ada tiga faktor yang mempengaruhi belum berkembangnya studi hadist, yaitu; Pertama, tidak terdapatnya guru-guru hadist yang mempuni. Kedua, keterikatan yang kuat terhadap mazhab merupakan salah satu kendala berkembagnya studi hadist. Ketiga, belum adanya perhatian dan keseriusan terhadap kajian hadist oleh akademisi yang ada.